The incorporation of vaults in the traditional housing of the inner Alentejo - Rosado, A. C. (Revista de História da Arte, 2025)
Almost unparalleled inside Portugal and akin only to neighbouring Spanish Extremadura, the incorporation of vertical brick vaults and timbrel vaults is a distinguishing feature of even the most common housing types in inner Alentejo. Research based on in loco architectonic and photographic surveys in four inner Alentejo cities combined with analysis of archive documentation from the 20th and 16th-18th centuries has produced data on the usage and types of vaults, including identification of the various types and geometries employed. This research proposes a chronology of vault construction in housing, indicating a likely beginning in the 17th century and its proliferation during the 18th century. Besides presenting the results, this paper examines various hypotheses to explain the transfer of an erudite technique into traditional housing by contextualising the historic and constructive moment of the Early Modern Age in Alentejo, with urban transformation due to warfare and consequent fortification.